Algebra

What is
5(- 3x - 2) - (x - 3) = -4(4x + 5) + 13

  1. 👍 0
  2. 👎 0
  3. 👁 75
  1. Multiply factors.
    -15x - 10 - x + 3 = -16x - 20 +13
    Group like terms.
    -16x - 7 = -16x - 7
    Add 16x + 7 to both sides and write the equation as follows
    0 = 0
    The above statement is true for all values of x and therefore all real numbers are solutions to the given equation.

    1. 👍 0
    2. 👎 1
  2. Hope it helps (;

    1. 👍 0
    2. 👎 0
  3. Answering yourself. How weird!

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response